Punch [videorecording (DVD)] - Roth, Tim; Oosterhof, Jordan; Hayes, Conan (Darkstar Pictures, 2023)
Jim is a promising teenage boxer, training under the watch of his demanding and alcoholic father. When Jim develops a relationship with a male classmate, the two are forced to navigate isolation, homophobia, and the brutality of small-town life. As Jim discovers what it means to be gay, he realizes how little strength has to do with heroism.